Promoting healthy eating: a brief review of predictors and interventions - Godinho, C. A. (2015)
Eating behaviours have an important impact on health and well-being. This paper presents research conducted by our group on the social psychology of eating and interventions for the promotion of healthy eating. Studies are presented on the social predictors of eating, such as the behaviour of others and cultural/social norms, and on the psychological predictors, motivational and volitional, as well as executive functions. Intervention studies using health messages and training of executive functions will also be described. Finally, the contribution of this work is discussed and directions for future research are outlined.